2022
DOI: 10.1038/s41398-022-01801-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and tryptophan metabolites can predict depressive symptoms in pregnancy

Abstract: Depression during and after pregnancy affects up to 20% of pregnant women, but the biological underpinnings remain incompletely understood. As pregnancy progresses, the immune system changes to facilitate fetal development, leading to distinct fluctuations in the production of pro-inflammatory factors and neuroactive tryptophan metabolites throughout the peripartum period. Therefore, it is possible that depression in pregnancy could constitute a specific type of inflammation-induced depression. Both inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 43 publications
6
59
0
Order By: Relevance
“…Excessive inflammation induces the tryptophan metabolizing enzyme, Indole Amine Pyrrole 2,3 dioxygenase, causing decreased production of serotonin in the synaptic cleft and at the same time increasing the production of neurotoxic substances through the kynurenine pathway [28]. A recent study proposes a model utilizing inflammatory cytokines and kynurenine metabolites that has > 99% probability of predicting depression in the third trimester [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Excessive inflammation induces the tryptophan metabolizing enzyme, Indole Amine Pyrrole 2,3 dioxygenase, causing decreased production of serotonin in the synaptic cleft and at the same time increasing the production of neurotoxic substances through the kynurenine pathway [28]. A recent study proposes a model utilizing inflammatory cytokines and kynurenine metabolites that has > 99% probability of predicting depression in the third trimester [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, the biological underpinnings of how these factors impact depression outcomes remain largely vague. Genetic vulnerability, sensitivity to changes in estrogen, progesterone, and cortisol levels are among the cited theories [4]. Recently, the inflammatory immune response has received special attention as an etiological mechanism for maternal depression [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, depressive symptoms appear in animal models when cytokine levels are experimentally elevated, for example, by injections of the bacterial endotoxin lipopolysaccharide ( Bay-Richter et al, 2011 ) or by poly I:C, which simulates a viral infection ( Gibney et al, 2013 ). Interestingly, depressed patients have, in some studies, been shown to have elevated plasma levels of pro-inflammatory cytokines ( Hestad et al, 2003 ), and it has been suggested that cytokine levels correlate with the severity of depression ( Sha et al, 2022 ). Furthermore, the HPA axis is known to be dysregulated in depression.…”
Section: Introductionmentioning
confidence: 99%